1972
DOI: 10.1038/237503a0
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Solar Particle Production above ∼75 GeV

Abstract: Observations of solar particles in the energy region above approximately 75 GeV provide good evidence for particle acceleration during the initial phase of a solar flare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1975
1975
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In the early of 1970s Stephen et al first reported their observation of solar particles with energies above $75 GeV in the initial phase of a solar flare [1]. In a very big solar cosmic ray ground level enhancement (GLE) event, on 29th September 1989, the Baksan group finally claimed that they observed about 20 GeV solar proton production from underground muon detector, although the excess appeared at 2 h later than the impulsive phase of the flare [2].…”
Section: Introductionmentioning
confidence: 99%
“…In the early of 1970s Stephen et al first reported their observation of solar particles with energies above $75 GeV in the initial phase of a solar flare [1]. In a very big solar cosmic ray ground level enhancement (GLE) event, on 29th September 1989, the Baksan group finally claimed that they observed about 20 GeV solar proton production from underground muon detector, although the excess appeared at 2 h later than the impulsive phase of the flare [2].…”
Section: Introductionmentioning
confidence: 99%
“…It is very interest to know whether there are still high energy solar proton beams and how high energies the solar protons can be accelerated in such big SPEs of non-GLE. In 1971 a positive correlation was obtained between a significant muon intensity increase and a specific solar flare by a narrow-angle telescope located at a underground mine in Colorado [26], although no response of NMs to this event. It is the first experiment evidence for solar particle production in above ∼75 GeV energy region in a solar flare of class M8.…”
Section: Introductionmentioning
confidence: 99%